Corrosion behavior of Mg wires for ureteral stent in artificial urine solution. (15th August 2021) - Mei, Di; Wang, Cheng; Nienaber, Maria; Pacheco, Margarida; Barros, Alexandre; Neves, Sara; Reis, Rui L.; Zhu, Shijie; Bohlen, Jan; Letzig, Dietmar; Guan, Shaokang; Zheludkevich, Mikhail. L.; et al.
Graphical abstract: Highlights: Corrosion behavior of Mg wires in artificial urine solution is investigated. The corrosion products with stratified structure are observed. Artificial urine solution possesses a strong pH buffer effect. Hydrogen evolution test cannot be used in this artificial urine solution. Abstract: Ureteral stents are a relatively new potential application for biodegradable Mg alloys. In this study, the corrosion behavior of Mg-1Zn wires and pure Mg wires in artificial urine solution (AUS) is investigated. It is found that AUS possesses a strong pH buffer effect. Hydrogen evolution measurement cannot be used for Mg corrosion test in this AUS due to the oxygen scavenging effect of sulfite, which is a component of AUS. The corrosion products consist of two layers, MgNH4 PO4 ·6H2 O and Mg(OH)2 . The partially protective MgNH4 PO4 ·6H2 O slows down the Mg corrosion, but it indicates the encrustation risk on bare Mg-based ureteral stents.